N-acetylcysteine reduces oxidative stress on end-organs in an ischemia-reperfusion rat model (Annals of Medical Research, 2021)
Aim: In this study, we researched the effect of N-acetylcysteine (NAC) on parenchymal organs in ischemia-reperfusion injury in the rat models. Material and Methods: Experimental animals divided into four groups: Sham group (Sh, n=6), Sham+NAC group (Sh+NAC, n=6), ischemia-reperfusion group (I/R, n=10) and N-acetylcysteine-given study group (I/R+NAC, n=10). For the Sham group and Sham + NAC group, only aortic exploration was performed. I/R group’s abdominal aortas were clamped just inferior to the renal artery for 4 hours following. Then, the reperfusion period was allowed for one hour. I/R+NAC group received the same procedure as I/R group and additionally treated with NAC intraperitoneally. After these procedures, all rats were sacrificed. The parenchymal organs were excised for biochemical, flow cytometric and histopathologic examination. The data were evaluated statistically.Results: In the I/R+NAC group, the MDA values in AC tissue were significantly lower than the I/R group (p:0.0032). MDA value in kidney tissue was significantly higher in the I/R group compared to the control groups (p:0.003). In the I/R+NAC group, the MDA value was significantly lower than the I / R group (p:0.0002). MPO values in lung tissue were found lower in the I/R+NAC group compared to the I/R group, it was not statistically significant (p:0.4497). In the I/R+NAC group, it was found statistically significantly lower than both the control and I/R groups in Flow cytometric evaluation (p:0.0002). In histopathological evaluation, the leukocyte count observed significantly higher in the I/R+NAC group compared to the control groups and was statistically significantly lower than the I/R group in histopathological evaluation (p:0,0004).Conclusion: NAC reduces ischemia and reperfusion injury in parenchymal organs and especially in the lungs in a rat model.